In vivo analgesic activity, toxicity and phytochemical screening of the hydroalcoholic extract from the leaves of Psidium cattleianum Sabine - Alvarenga, Felipe Queiroz; Mota, Bárbara C.F.; Leite, Marcel N.; Fonseca, Jaciara M.S.; Oliveira, Dario A.; de Andrade Royo, Vanessa; e Silva, Márcio L.A.; Esperandim, Viviane; Borges, Alexandre; Laurentiz, Rosangela S. (Elsevier, 2013)
Ethnopharmacological relevance: Psidium cattleianum Sabine is extensively used in Brazilian traditional medicine to treat several diseases including painful disorders. Aim of the study to investigate the toxicity and the possible analgesic activities of the hydroalcoholic extract from the leaves of Psidium cattleianum Sabine (ELPCS), to support its use in folk medicine. To screen the major phytochemical constituents of this extract and evaluate their antioxidant activity. Materials and methods: ELPCS was assessed for its antioxidant activity using the DPPH model. Its analgesic activity was examined using mouse models of acetic acid-induced writhing and hot plate paw licking models. The major phytochemical constituents of the extract were screened; their toxicity on LLC-MK2 mammalian cells was evaluated. Results: ELPCS exhibited significant peripheral analgesic activity at doses of 60, 80, 100, 200 and 400 mg/kg in mice, but it did not display central analgesic activity and not was toxic to LLC-MK2 cell (LD 50>400 μg/mL). The extract exhibited free radical scavenging activity as evidenced by IC 50 values (15.9 μg/mL) obtained by the DPPH method. Phytochemical screening detected flavonoids, saponins, cardiac glycosides, anthraquinones, and tannins. Conclusions: The results of the experimental studies proved the analgesic activity of ELPCS and supported the traditional use of this plant. © 2013 Elsevier B.V. All rights reserved.
Keywords: Analgesic activity; Myrtaceae; Phytochemistry; Psidium cattleianum Sabine; Toxicity